PENINGKATAN KAPASITAS PUBLIC SPEAKING BAGI APARATUR PEMERINTAH DESA TANJUNG DAYANG SELATAN - Mery Yanti; Rindang Senja Andarini; Muhammad Nur Budiyanto; Raniasa Putra; Diyaz Syauki Ikhsan; Ayu Purnamasari (Universitas Mataram, 2023)
Background: The ability to speak in public needs to be mastered by anyone, including village government officials. Not only the apparatus, all elements involved in the village including the Karang Taruna, the Village Representative Body, and the Empowerment and Family Welfare (PKK) of the village need to improve public speaking skills in order to strengthen the village's potential and self-potential. The absence of public speaking learning facilities in the village environment limits the local community's opportunities to develop public speaking skills. Purpose: Therefore, this community service activity aims to improve the public speaking skills of South Tanjung Dayang village apparatus, Indralaya Selatan District, Ogan Ilir Regency, South Sumatra Province. Method: This activity is aimed at village government officials which is carried out using three methods: lectures and questions and answers regarding the basic aspects of public speaking; problem solving by opening discussions about the participants' concrete problems when speaking and solutions to overcome them, as well as demonstrations and simulations. Result: This community service shows that this activity succeeded in increasing participants' understanding of important aspects of public speaking. This can be seen from the average score of the participants during the pre-test which increased from 69.2 with the lowest score of 35 to 85.6 with the lowest score of 65 during the post-test. Statistical analysis using the Wilcoxon test showed that the Sig. (2-tailed) of 0.000 <0.05 which means the alternative hypothesis (Ha) that there is a significant difference between the average pre-test scores and post-test scores has been proven. This shows that public speaking training has a significant influence on increasing the understanding of the participants. Conclusion: The implementation of public speaking training for Tanjung Dayang Selatan village officials as a whole has been successful because there has been a significant increase in understanding.